Uji Efektivitas Tanaman Refugia dalam Menurunkan Intensitas Serangan Lalat Buah pada Cabai Rawit - Albertus Edy Kurniawan; Andree Wijaya Setiawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Fruit flies (Bactrocera spp.) are pests that attack cayenne peppers, with attacks reaching 100%. Generally, farmers use synthetic insecticides, but in the long term this can disrupt the balance of the ecosystem and trigger pest outbreaks and resistance—integrated pest control by planting refugia as a micro-habitat for natural enemies. Marigolds and zinnias were chosen as refugia plants. The aim of the research was to determine the types of fruit flies that attack chili plants, the symptoms of fruit fly attacks on chili fruit, the effectiveness of marigold and zinnia plants in reducing the intensity of chili plant attacks, and external factors that influence the efficacy of refugia marigold and zinnia plants. The research was conducted in July – October 2023 in Jlarem Village, Gladaksari District, Boyolali Regency, using a Randomized Block Design (RAK) with four treatments, namely control, marigold, zinnia, and a combination of both, using six replications so that there were 24 experimental units with ten plants in each experimental unit. This research used a hygrometer thermometer (HTC2), camera, net, and binocular microscope. Observation variables include the type of fruit fly, attack symptoms, attack intensity, and external factors. The types of fruit flies found in the study area were Bactrocera dorsalis, Bactrocera umbrosa, and Bactrocera carambolae. Symptoms that arise due to fruit fly attacks on chili fruit are black spots on the skin of the fruit, which become more expansive over time, causing the fruit to rot and fall prematurely. Refugia planting effectively reduced the intensity of fruit fly attacks, with the lowest attack intensity in the combination treatment of marigold and zinnia at 22.16%. Several external factors influence the effectiveness of refugia in controlling fruit flies, namely environmental temperature and humidity and the types of plants growing around the cultivated land.